IMPACT OF SIMPLE VIRTUAL TECHNOLOGY APPLICATION IN ARCHITECTURAL EDUCATION - Bramasta Putra Redyantanu; Altrerosje Asri (DIMENSI (Journal of Architecture and Built Environment), 2021)
The development of technology cannot be separated from the development of science, including the learning method. There is an elective course named Virtual Reality Architecture in Architecture Department of Petra Chrisitan University. This course focuses on the process of learning architecture at the stage of presenting and communicating ideas. The virtual technology used as a learning method includes three types of technology, animation, augmented reality and virtual reality. The three technologies are elaborated as a simulation method. The simplicity of its application can be seen in the support for hardware, software, and special devices used by students in their daily lives. This study aims to test the achievement of goals at the final level of learning. Students who have attended this lecture are then interviewed and observed, in relation to proving whether this simple virtual technology can be a supporter in the learning process in the architecture study program.